Measure the impact of contribution of Saudi Women's- in private sector- on economic growth for period 2005- 2017 - Elhassan, Tomader Gaber Elbashir (Journal of Economic, Administrative and Legal Sciences, 2020)
The main objective of this study was to measure the impact on the contribution of Saudi women working in private the sector on economic growth for period 2005- 2017, In spite of the difficulties and challenges facing women contribute to the private and public sectors. It based on the following hypotheses: There was a statistically significant relationship between economic growth and Women's contribution of industry, trade, insurance and real- estate services, and community services in the long and short- run. The study used a descriptive approach and the methodology of econometrics to construct the model and Eviews10 Program for data analysis. The Data was collected from the Saudi Arabian Monetary Authority, for the period (2005- 2017). It used the bounds testing (ARDL) Method to estimate Women's contribution equation. The results were explained that was a statistically significant relationship between the Women's contribution to trade, insurance and real- estate services and economic growth in the long. The weakness of elasticity was due for: the study period was short and recently, Women participated in the private sector. In Short- run economic growth was affected only by the contribution of women to trade. There was a statistically insignificant relationship between the Women's contribution to the service of the community and economic growth in the long and short- run. The error correction indicated that the shock in the past year is corrected in the current year. The study recommended were the follows: The implementation of training courses to increase the Women's contribution of industry and community services in the long and short- run. Activate systems that encourage women to work in private sector. For future study Researcher recommends applying the detailed study to measure the impact on the Women's contribution to all activities of the private sector.
Keywords: Vision 2030; workforce; integration; Douglas Cobb; autoregressive